Descripción y morfología de dos cráneos de tortugas terrestres del género chelonoidis del mioceno de La Venta, Huila, Colombia (2020)
The locality of La Venta is one of the most important paleontological sites in northern South America, characterized by its richness of fossils from the middle to late Miocene (~16-11 Ma). A great variety of vertebrate specimens have been found in this fossiliferous zone of the middle Miocene, including several species of turtles, belonging to the suborder Pleurodira and Cryptodira. The fossil record of turtles in La Venta indicates that most of the turtles of the middle Miocene were Pleurodira and had an aquatic lifestyle, but some specimens of terrestrial turtles (tortoises), belonging to the genus Chelonoidis have also been found, which represent the only cryptodiran (hidden-necked turtle) from this region. So far, two possible species of Chelonoidis existed in La Venta but only one has been partially described, C. hesterna. Still, much is unknown about these tortoises from the middle Miocene of Colombia. Therefore, this study aims to analyze and expand the morphological description of the Chelonoidis fossils with two new skull specimens found in the locality of La Venta, Huila, Colombia. In this study, we found that the two new Chelonoidis specimens resemble in size to Chelonoidis sp. indet, and that most of the cranial bones have typical contacts of the genus Chelonoidis in relation to the shape, proportion and sutural contact.